STYLISTIC AND SEMANTIC NUANCES OF SYNONYMOUS PSYCHOLOGICAL TERMS IN THE UZBEK LANGUAGE (Web of Teachers: Inderscience Research, 2025)
This paper analyzes the stylistic and semantic differences among synonymous psychological terms in the Uzbek language, focusing on the words tashvish, havotir, and bezovtalik. Although often treated as equivalents, these terms vary in tone, usage, and emotional intensity. The study is based on a descriptive linguistic analysis using examples from Uzbek texts, dictionaries, and media sources. Findings suggest that synonymy in psychological vocabulary reflects both linguistic and cultural nuances, which are important for effective communication, translation, and psychological education.